PENCEGAHAN TRAFIKING DAN REHABILITASI SOSIAL TERHADAP ANAK SEBAGAI KORBAN - Anak Agung Adi Lestari (Jurnal Hukum Saraswati (JHS), 2019)
Prevention of trafficking in persons, especially women and children, is a part of human rights for children and women. The importance of handling child trafficking is based on the increase in the number of cases estimated by UNICEF each year around 1.2 million children in Asia, there are around 400,000 children who have been victims of trafficking in which around 70,000 children are sexually exploited. Based on the description, there are several problems, namely, first, how is the government's effort in tackling the trafficking of children, second, what factors cause trafficking in children. Trafficking in children is an act that deprives children of their rights. This contradicts article 34 of the 1945 Constitution which states, "The poor and neglected children are banned by the state". Government efforts are urgently needed to deal with the problem of trafficking in abandoned children so that they get a legal protection. Factors that support the occurrence of trafficking are: low education, unemployment, weak law enforcement, free lifestyles, the amount of interest regarding commercial sex workers, pornographic writings and so on. In this case the government can take an action outside the law but not deviate from the values that exist in handling the case.